Testicular diffuse large B-cell lymphoma. Clinical lecture and case report - K. B. Lelyavin; A. V. Taranenko; V. G. Bryukhanov (Acta Biomedica Scientifica, 2023)
Lymphoma is a heterogeneous group of lymphocyte malignancies that may involve lymphatic tissue, bone marrow, or extranodal sites. The lecture provides a  brief overview of the current state of the problem of diagnosis and treatment of primary testicular lymphoma. Primary testicular lymphoma (PTL) is a rare lymphoid malignancy. Though it is rare, PTL is the most common type of testicular tumor in men over 60 years of age. The most common histological type is diffuse large B-cell lymphoma. To date, there are no well-documented etiological or risk factors for PTL. In contrast to other common testicular neoplasms, there was no statistically significant association of PTL with cryptorchidism, trauma, chronic orchitis, or infertility. Ultrasound is generally the first-line imaging method used to characterize testicular lesions. PTL manifests itself in the form of a hypoechoic formation, which can take the form of either a single large formation or multiple small formations that occupy most of the testicular parenchyma or completely replace it. Systemic treatment, including orchiectomy, chemotherapy, radiation therapy, and intrathecal prophylaxis, is necessary for all patients with PTL. In addition to achieving complete remission, the goal of PTL treatment is to prevent recurrences in the contralateral testis and central nervous system. The presented information is supplemented by our own observation and images. Personal medical data is published with the written consent of the patient. In our case, the patient’s age was 38 years, which does not fall into the specified age group for primary testicular lymphoma. In our opinion, the publication of this clinical case and analysis of scientific literature on this topic are relevant.